The Norwegian Seamen's Church: Lady Hailes Road, San Fernando, Trinidad, W.I. - (:unkn) unknown (My University, 2010)
Image depicts a scenic, bird's eye view of the Norwegian Seamen's Church, located on Lady Hailes Avenue, in the city of San Fernando on the island of Trinidad, The Republic of Trinidad and Tobago. Postcard number K-16339.
Colour: Shades of Green Blue, Brown and Yellow; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Church buildings--Trinidad and Tobago; Buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--San Fernando; Bodies of water--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Streets--Trinidad and Tobago; Architecture--Trinidad and Tobago; Church Architecture--Trinidad and Tobago; Seas--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Plants--Trinidad and Tobago; Lady Hailes Avenue (San Fernando)